Study of Marketing Campaign Model to Increase Egg Consumption - Syahlani, Suci Paramitasari; Muzayyanah, Mujtahidah Anggriani Ummul; Haryadi, F. Trisakti; Nurtini, Sudi (2017)
This study was intended to assess (1) knowledge and the preferences of elementary school - aged in low income family in regards to eggs (2) to evaluate marketing campaign model that aimed to the increasing of eggs. The research was conducted in Gadjah Wong urban communities in Umbulharjo Subdistrict, Yogyakarta City and Candibinangun in Pakem Subdistrict, Sleman Regency which were two villages with the highest number of low - income family. Sample was determined by judgmental sampling method that w ere mothers aand the children who were elementary school - aged children. The results show majority of children have good knowledge about eggs benefit, but however only 2.00 % children preferred to eat, 15.30 is neutral and majority that is 82.60% respondent s do not like to eat eggs . Pattern of eggs consumption either from rural and urban areas reveal consistent results that eggs are part of the staple food for the children even still in smal number. 90.20% children reported that at least they have two eggs i n a week. The increase of egg consumption as an affordable source of protein is still hindered by the huge proportion of children that disapprove the consumption of egg. To overcome that issue, improvements for marketing communication model is required giv e experience to mothers as the one who create buying decision and also to increase the skills to cook egg s in more innovative ways . Keywords : Marketing campaign, Eggs, Low income family